What Candy Crush Saga Teaches Us About Motivating Employees. Issue 4 (April 2015) - Bedard, Ana T.
Abstract : Businesses are bringing game elements into the workplace to motivate employees to engage in initiatives from learning to quality improvement. Grounding gamification theory in experience, I examine the popular game Candy Crush Saga. Candy Crush contains four design elements that managers can bring into the workplace to more successfully motivate workers: It provides early and progressively bigger successes, actively celebrates your victories, provides help if you need it, and provides a vision for the future.